Perancangan Ulang Tata Letak Fasilitas Guna Memaksimalkan Produktivitas Kerja Pada Toko Sukses Bersaudara - Gina Jaudah; Aulia Mardatila; Amirah Hamidah; Muhammad Rizky Raihan Aziz (Jurnal Bisnis Kreatif dan Inovatif, 2024)
Today's business developments are increasingly diverse, including retail businesses. Retail in Indonesia is currently growing rapidly. In every corner of the city, it cannot be denied that many retail shops have been built, not only to make a profit but also to provide facilities to the community which is also growing and has more and more needs that must be met. Retail is one of the retail stores in Indonesia which is currently developing. To make work and activities easier, the Blue Green Line Shop needs to improve its spatial layout. The spatial layout that the shop has designed is still considered less effective and efficient. Due to the placement of the freezer which is not visible to customers and the refrigerator which blocks the cashier, it disturbs customers in the payment process. The methods used are the ARC (Activity Relationship Chart) and TCR (Total Closeness Rating) methods. The results of this research show that the cashier has the highest score from the TCR calculation results, namely 168 and has an influence on the course of shop activities using the TCR worksheet, as well as the proposed placement of the freezer right next to the entrance so it is not visible and the refrigerator blocks the cashier from being moved to another row of refrigerators, so that work and activities can run as they should.